Legal Counseling on National Health Insurance as the Fulfillment of the Right to Public Health in Singasari Village, Jonggol District, Bogor Regency, West Java, Indonesia - Rr. Ani Wijayati; Haposan Sahala Raja Sinaga; Radisman Saragih; Edward M.L. Panjaitan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Community service is carried out by the Faculty of Law at the Christian University of Indonesia by providing legal counseling on national health insurance as fulfillment of the right to public health. This activity was held by the Singasari Village Office which is located at Jl. Cihaur Raya No. 17 Jonggol, Bogor. The method used is to provide counseling/lectures. The results legal counseling are “very effective considering that there are still many people who do not get information on the national health insurance provided by the Government. With this legal counseling, the community will become aware of this program and what benefits can be obtained, such as the existence of multiple benefits, medically and non-medically.”